Great Britain and the War of the Triple Alliance: The Lincolnshire Farmers Colonization Scheme to Paraguay and the Fourth Ally Thesis. - Nickson, Andrew (Hispanic American Historical Review, 2024)
This article challenges the fourth ally thesis, which argues that Great Britain was a crucial actor underpinning the combined forces of Argentina, Brazil, and Uruguay that defeated Paraguay in the 1864–70 War of the Triple Alliance. To date, the debate has focused on British involvement in the genesis and financing of the allied war effort. This article instead focuses on the postwar behavior of the British government, exploring its attitude to the 892 mainly English colonists of the failed 1872–73 Lincolnshire farmers emigration scheme to Paraguay. The British government's open hostility to the scheme and its lack of concern for the plight of the colonists offer new evidence suggesting that the War of the Triple Alliance was of little interest to British imperialism in general and to settler colonialism in particular.